(The effect of deterpenation process on the medicinal quality of nutmeg oil) - Sait, Salya; Satyaputra, Inggriani (Warta Industri Hasil Pertanian, 1995)
To study the effect of deterpenation process on the medicinal quality of nutmeg oil (Myristica fragrans Houtt), the alcoholic extraction as well as the chomatographic separation technique of deterpenationwas employed on some crude nutmeg oil.Result of the experiment concluded that either the alcoholic extration or the chromatograpic separation technique of deterpenation caused a down grade of the medicinal quality of nutmeg oil due to an increase in the level of myristicin concentration. The former technique gave a complete removal of monoterpene hydocarbon and the latter gave only partial removal.